2005
DOI: 10.1074/jbc.m414508200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Vinorine Synthase, the First Representative of the BAHD Superfamily

Abstract: Vinorine synthase is an acetyltransferase that occupies a central role in the biosynthesis of the antiarrhythmic monoterpenoid indole alkaloid ajmaline in the plant Rauvolfia. Vinorine synthase belongs to the benzylalcohol acetyl-, anthocyanin-O-hydroxy-cinnamoyl-, anthranilate-N-hydroxy-cinnamoyl/benzoyl-, deacetylvindoline acetyltransferase (BAHD) enzyme superfamily, members of which are involved in the biosynthesis of several important drugs, such as morphine, Taxol, or vindoline, a precursor of the anti-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
182
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(191 citation statements)
references
References 39 publications
(25 reference statements)
8
182
0
1
Order By: Relevance
“…responsible for the biosynthesis and natural variation of benzoylated tryptamine/serotonin. Previous crystal studies have identified several amino acid residues in the N-and C-terminal regions of BAHD acyltransferases important for differential acylacceptor specificity (Ma et al, 2005;Unno et al, 2007;Lallemand et al, 2012;Walker et al, 2013). Here, comparative sequence analysis with in vitro assays using mutant enzymes led to the identification of a RRRR motif that is sufficient to transform agmatine utilization ( Figures 9A and 9B), which is similar to the conserved arginine-rich motifs in RNA binding proteins (Lazinski et al, 1989;Zapp et al, 1991;Yuryev et al, 1996).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…responsible for the biosynthesis and natural variation of benzoylated tryptamine/serotonin. Previous crystal studies have identified several amino acid residues in the N-and C-terminal regions of BAHD acyltransferases important for differential acylacceptor specificity (Ma et al, 2005;Unno et al, 2007;Lallemand et al, 2012;Walker et al, 2013). Here, comparative sequence analysis with in vitro assays using mutant enzymes led to the identification of a RRRR motif that is sufficient to transform agmatine utilization ( Figures 9A and 9B), which is similar to the conserved arginine-rich motifs in RNA binding proteins (Lazinski et al, 1989;Zapp et al, 1991;Yuryev et al, 1996).…”
Section: Discussionmentioning
confidence: 63%
“…The biological significance underpinning the convergent evolution of aryldiamine acyltransferases from both BAHD and GNAT families of proteins, especially within Gramineae, requires further investigation. The 3D structures of some BAHD acyltransferases have been resolved (Ma et al, 2005;Unno et al, 2007;Garvey et al, 2008;Lallemand et al, 2012;Manjasetty et al, 2012;Walker et al, 2013), but no structures are yet available for N-acyltransferases. Elucidation the structure of BAHD N-acyltransferase will greatly facilitate understanding these divergent and convergent evolutionary paths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HCT belongs to the BAHD family of plant acyl-CoAdependent acyltransferases, which possess a conserved HxxxD motif (Burhenne et al, 2003;Ma et al, 2005;D'Auria, 2006). The residue His (H) in the HxxxD motif is important for the enzymatic activity of HCT, and mutation of this amino acid greatly reduces its catalytic activity (Lallemand et al, 2012;Walker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%